2017
DOI: 10.5847/wjem.j.1920-8642.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The presenting and prescribing patterns of migraine in an Australian emergency department: A descriptive exploratory study

Abstract: BACKGROUND:Migraine is a common neurological condition that frequently presents to the emergency department (ED). Many medications are available to treat migraine. This study aims to characterize the demographics of patients who present to a large metropolitan ED with migraine, and to identify the medications used in treating this condition. METHODS:This study is a retrospective database interrogation of clinical records, used to collect quantitative data on patient demographics and medication prescriptions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Our study period of 5 years, in addition to two previous 12‐month and one 3 year study, strengthens our understanding of ED prescribing patterns over time. Our findings add to the existing international literature regarding the need for improvement in acute migraine management in EDs worldwide, with similarities in findings suggesting that a common approach to improvement strategies may be possible.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our study period of 5 years, in addition to two previous 12‐month and one 3 year study, strengthens our understanding of ED prescribing patterns over time. Our findings add to the existing international literature regarding the need for improvement in acute migraine management in EDs worldwide, with similarities in findings suggesting that a common approach to improvement strategies may be possible.…”
Section: Discussionsupporting
confidence: 68%
“…Two studies, almost a decade apart, found that there was wide heterogeneity in prescriptions for acute migraine, with low rates of triptan use and common opioid prescription . This finding was confirmed in a more recent Australian study which investigated prescription differences between first and repeat presentations to ED with migraine; it concluded that first time presentations are investigated more heavily but did not receive any significantly different prescriptions …”
Section: Introductionmentioning
confidence: 86%
“…This included: 57% ( n = 8) from the United States, 21% ( n = three) from Australia and 7% ( n = one) from Pakistan, France, and Canada. The study population with migraine ranged between 78 [ 18 ] and 2228 [ 1 ] subjects. Most migraineurs presenting to ED were young and female with average age ranges between 32.5 [ 18 ] and 44.5 [ 19 ] years and females consisting between 64% [ 27 ] and 85.9% of patients [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Migraine headache is a common, debilitating, and costly neurological disorder, affects up to 16.6% of the general population [ 1 ] and is recognized as the second most disabling condition in the world according to disability adjusted life years [ 2 ]. Beyond individual wellbeing and suffering, migraine is a public health issue that puts a burden on society through healthcare system and productivity costs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ESR1 rs1801132 (325C>G) is positively associated with migraine in a Spanish population. ESR1 rs2228480 (594G>A) carries a higher risk for migraine in an Australian population, whereas ESR1 rs2234693 is associated with migraine susceptibility in a Chinese population [ 23 ]. The neuronal etiology of migraine is described by increased ascending signaling and diminished descending inhibitory signals [ 24 ].…”
Section: Genetic Polymorphisms Influence On Chronic Pain Conditionmentioning
confidence: 99%